Pharmacoepidemiological study of the safety of drug use in children by analyzing the Russian database of spontaneous reports - A. R. Titova; I. L. Asetskaya; V. A. Polivanov; S. K. Zyryanov (Izdatelstvo OKI, 2018)
Purpose. To study the structure of serious adverse drug reactions and «off label» drug use in children by means of analysis of the national pharmacovigilance database. Materials and methods. We analyzed 341 spontaneous reports about serious adverse reactions in children, submitted to the Russian pharmacovigilance database in 2012, and 467 suchlike spontaneous reports registered in 2015. Results. Children of preschool age have higher risk of medical therapy complications. Most frequently, skin (33,4% in 2012 and 38,7% in 2015) and organism as a whole (21,4 and 21,1%, respectively) were involved in the pathological process. Antimicrobial drugs for systemic use (43,5% in 2012 and 43,8% in 2015) and drugs for nervous system (25,1 and 26,1% respectively) often caused them. Unexpected serious adverse reactions accounted for 16,9% of all complications in children in 2012, 10,8% in 2015. It was established that 58,7% of suspected medicines in 2012 and 47,5% in 2015, the use of which was associated with the development of serious complications in pharmacotherapy in children, were prescribed with deviations from the recommendations of approved prescribing drug information. The main types of «off-label» drug use were inappropriate indications, deviations from the recommended dosage regimen, the use of a drug in the age group of patients, wherein the drug has not been approved, and the use of a drug in the presence of contraindications to its use. Conclusion. Our research confirms that the practice of «off-label» drug use in children is an independent risk factor for developing adverse drug reactions. It is shown that the method of spontaneous reporting can help to identify the problems of drug safety and to develop recommendations for minimizing the risk of complications of pharmacotherapy in pediatric practice.